Comparative analysis of resection boundaries depending on the defect elimination method in oral mucosal cancer - Sh. I. Musin; K. V. Menshikov; A. V. Sultanbayev; I. A. Sharifgaleev; V. V. Ilyin; A. O. Guz; A. N. Rudyk; S. V. Osokin; N. A. Sharafutdinova; A. V. Chashchin; A. V. Garev; T. R. Baymuratov (Опухоли головы и шеи, 2024)
Introduction. Surgical intervention remains the main method for treatment of the oral mucosa cancer. The generally accepted standard of the resection boundary that provides optimal local control is 5 mm. Adequate boundaries of indentation and choice of the reconstruction method are important issues facing specialists in head and neck tumors.   Aim. To evaluate parameters of the resection edge in the surgical treatment of malignant neoplasms of the oral mucosa depending on the method of eliminating of the post-resection defect and its effect on the frequency of local relapse.   Materials and methods. A retrospective analysis included 168 primary patients (50 % men and 50 % women) who received surgical treatment in the head and neck tumor department of the Republican Clinical Oncology Dispensary of the ministry of Health of the Republic of Bashkortostan (ufa) from 2019 to 2023. The median age of patients was 63 years (interquartile range (IQR) 55–69 years). most often, the primary tumor was located in the tongue – in 59.5 % (100/168) of cases. According to the method of post-resection defect removal, the patients were divided into 3 groups. In group 1, reconstruction was performed with local tissues (n = 71), in group 2 – with pedicle flaps (n = 41), and in group 3 – with revascularized flaps (n = 56). The median follow-up period was 18 months (IQR 8–28 months).   Results. Resection boundaries in group 1 were 7.0 mm (IQR 5.0–12.5 mm), in group 2 – 6.5 mm (IQR 5–13 mm), and in group 3 – 12.5 mm (IQR 7.5–15.0 mm). The overall frequency of near/positive resection boundaries was 14.8 % (25/168). In group 1, it was 15.5 % (11/71), in group 2 – 19.5 % (8/41), in group 3 – 10.7 % (6/56). According to the analysis, relapse of the disease after radical treatment was noted in 32 % (55/168) of patients, of which 14.8 % (25/168) had a local relapse, 12.5 % (21/168) had a regional relapse, and 5.4 % (9/168) developed distant metastases. The frequency of local relapse in group 1 was 18.3 % (13/71), in group 2 – 23.8 % (10/41), in group 3 – 5.5 % (3/56). According to the analysis data, statistically significant differences in the boundary of indentation in the groups were revealed depending on the reconstruction method (p = 0.005).   Conclusion. Based on the results of the present retrospective analysis, the choice of reconstruction method affects the resection boundary in real clinical practice. Limitations in the surgical indentation that surgeon faces when choosing a method for eliminating a post-resection defect are demonstrated.